Clinical management and successful pregnancy outcomes in women with empty Sella syndrome undergoing assisted reproductive technology: a case-based approach - Mariyappan, Scindiya; Anand, Papitha P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Empty Sella syndrome (ESS) is a radiological condition characterized by a partially or completely flattened pituitary gland within the sella turcica, which may impact reproductive function. This case report presents two women with ESS undergoing in vitro fertilization (IVF). Despite having ESS, patient A had a normal ovarian reserve and conceived after frozen embryo transfer (FET) and regulated ovarian stimulation. Patient B needed an oocyte donation program in order to achieve pregnancy because of their significantly reduced ovarian reserve (AMH=0.01 ng/ml). The fact that both patients were able to conceive shows how important it is to use customized assisted reproductive technology (ART) plans depending on ovarian function. ESS presents a heterogeneous impact on fertility, necessitating tailored treatment plans, including optimized ovarian stimulation, embryo transfer protocols, and donor oocyte utilization. A multidisciplinary approach involving reproductive endocrinologists and fertility specialists is crucial in managing ESS-related infertility to maximize pregnancy success.